Study of factors influencing construction delays at rural area in Malaysia - Ramli, M Z; Malek, M A; Hanipah, M. H.; Lin, C L; Mahamad Sukri, M F; Zawawi, M H; Zainal Abidin, M Z; Mohamad Fuad, N F S (INSTITUTE OF PHYSICS PUBLISHING, 2018)
Construction is one of an important industry which contributes to the economic growth in Malaysia. However, it has been revealed that 79.5 percent and 66.7 percent of the public and private projects were not completed within the time specified in the contracts out of 359 projects in Malaysia. Therefore, the purpose of this study is to investigate the delay factor caused project delay at rural area. A 5-points Likert scale questionnaire survey were answered by 111 respondents which having experience with rural construction project. The questionnaire data were analysed by using Relative Importance Index (RII). Five top factors were determined from this study based on their RII values which are improper construction method implemented by contractor, weather condition, difficulties in providing delivery to site, breakdown of site equipment, and poor qualification of contractor’s technical staffs.